Pemberdayaan Kelompok Wanita Tani Masyarakat Kalikebo melalui pengoptimalan fungsi pekarangan - Kartikasari, Chintya; Kuncari, Hastin Setya; Nafriyatun, Khoirin; Ahmad, Labib Dzulqurnain; Husna, Siti Shoinatul; Hasan, Farid (Penamas: Journal of Community Service, 2024)
Many efforts need to be made to improve the community's economy, one of which is maximizing land use. However, in reality, the use of home gardens in the community is not optimal, and productivity still needs to improve, so empowerment is needed. Community service and empowerment activities aim to improve the economy of women farming groups in Kalikebo Hamlet, Rejosari Village, Bandongan District, Magelang Regency, with the hope that the welfare of the residents will gradually increase. The methodology in this service activity uses an Asset-Based Community Development approach, the activity stages of which include the approach stage, vegetable cultivation counseling stage, mentoring stage, and results. Activities include counseling on yard use, providing vegetable seeds and polybags, and other activities. The results of community service activities were responded to very well, and the women farmer group was very interested in the program to use yards for growing vegetables. The final result of this activity is planting vegetables in the participants' yards, which grow well and can reduce family expenses.